Prevalence and risk factors of abortion among a sample of married women in Kurdistan Region of Iraq - Azo, Fatema Mohammed; AKBAY, Cuma A. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: A high proportion of maternal mortality in developing countries is caused by abortion, especially in such countries with limited abortion laws. The aim of this study was to determine the prevalence of abortion and investigate the relationship between abortion among women and their socio-demographic and obstetrical causative variables in Kurdistan Region of Iraq. Methods: The data for the research came from 7551 married women aged 15-49 years from three governorates of Kurdistan Region who participated in the 2011 multiple indicator cluster survey. Data were collected during the period from February 13th, to March 18th, 2011 in the Kurdistan region. Logistic regression analysis was done at the binary level to determine the effect of demographic and obstetrical factors on abortion. Results: The results showed that the prevalence of abortion in this study was 27.7%, and there was statistically significant relationship between abortion and maternal age, the higher level of education, socio-economic levels (excluding middle level), the age of marriage, the number of live children, and governorate (Duhok). There was no significant relationship between abortion and residence, occupation, type of marriage and governorate (Suleymaniye). Conclusion: Significant relationship was found between ages, the number of live children, Residence, level of education and social economic status of women.